Lipid droplets, bioenergetic fluxes, and metabolic flexibility. (December 2020) - Bosch, Marta; Parton, Robert G.; Pol, Albert
Abstract: The capacity of cells and animals to sense and adapt to fluctuations in the availability of energetic substrates is commonly described as metabolic flexibility. This flexibility allows for example the transition from fed to fasting states and to meet the energy demands of exercise in both states. Flexibility is disrupted in pathological conditions such as the metabolic syndrome but in contrast, it is enhanced in some tumours. Lipid droplets (LDs) and mitochondria are key organelles in bioenergetics. In all eukaryotic cells, LDs store and supply essential lipids to produce signalling molecules, membrane building blocks, and the metabolic energy needed to survive during nutrient poor periods. Highly conserved, robust, and regulated mechanisms ensure these bioenergetic fluxes. Although mitochondria are recognized as the epicentre of metabolic flexibility, the contribution of LDs and LD-proteins is often neglected or considered detrimental. Here, we revisit the key roles of LDs during fasting and the intimate collaboration existing with mitochondria when cells sense and respond to fluctuations in substrate availability.